Aktivitas Antioksidan dan Toksisitas Senyawa Bioaktif dari Ekstrak Rumput Laut Hijau Ulva reticulata Forsskal - Swasono R. Tamat; Thamrin Wikanta; Lina S. Maulina (JURNAL ILMU KEFARMASIAN INDONESIA, 2007)
Research on the antioxidative activity and toxicity of the bioactive substance of the green seaweed Ulva reticulata Forsskal extract had been carried out. The bioactive substance of the green seaweed Ulva reticulata Forsskal was extracted using methanol. The phytochemistry test on the methanol extract showed that the extract contained triterpenoid compound. The methanol extract was then partitioned using n-hexane-water (1:1) and chloroform-water (1:1). Each of the extract was then dried using freeze dryer. The antioxidative activity test of each fraction against free radical 1,1-diphenyl-2-picrilhydrazil (DPPH) showed that the water extract has the highest activity with IC 30 of 365,95 ug/ml. The toxicity test of each fraction against brine shrimp Artemia salina (Brine Shrimp Lethality Test, BSLT) showed that the chloroform extract showed the highest activity with LCs of 250,67 ug/ml. The water extract was then fractionated through silica column chromatography. The activity test of each fraction against DPPH and BSLT showed that fraction 1 has the highest activity with LCs of 100 ug/ml and ICs of 270,31ug/ ml. Identification using gas chromatography – mass spectrometric method showed that the antioxidative substance presence in the active fraction was probably nonyl phenol (C, H2,0).